Gajah Mada, Patih Agung yang Berperan dalam Menyatukan Nusantara pada Masa Kekuasaan Kerajaan Majapahit antara Tahun 1336 hingga 1359 Masehi - Syarfira; Lr Retno Susanti; Hudaidah (PT PUBLIKASI INSPIRASI INDONESIA, 2025)
Gajah Mada is one of the most influential figures in Indonesian history, especially during the height of the Majapahit Empire in the 14th century. As the Patih Agung under King Hayam Wuruk (1336–1359 AD), Gajah Mada played a key role in expanding the Majapahit territory and realizing his vision of uniting the archipelago through military expansion and diplomacy. Through his legendary Palapa Oath, Gajah Mada demonstrated his determination to refrain from personal pleasures until the entire archipelago was united under Majapahit rule. In the process, he successfully integrated smaller kingdoms in regions such as Sumatra, Bali, Kalimantan, and Maluku, strengthening Majapahit's position as a dominant power in Southeast Asia. Gajah Mada's success in unifying the archipelago left an important legacy in the political, cultural, and administrative development of the Majapahit Empire. This article examines Gajah Mada's leadership journey, the expansion strategies he implemented, and the long-term impact of his rule on the stability and development of Majapahit. Although the empire eventually declined, Gajah Mada's vision and spirit of unity continue to be an integral part of the national identity of Indonesia to this day.